2008
DOI: 10.1002/jsfa.3226
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative capacity produced by Bifidobacterium‐ and Lactobacillus acidophilus‐mediated fermentations of konjac glucomannan and glucomannan oligosaccharides

Abstract: BACKGROUND: Konjac glucomannan (KGM) has been shown to stimulate the growth of bifidobacteria and lactobacilli in the human and rat colon. This study investigated the antioxidative effects produced after 48 h in vitro fermentation of unhydrolysed KGM and two hydrolysed KGM fractions (KH1 and KH2 with degree of polymerisation 10 and 5 respectively) by Bifidobacterium adolescentis, B. bifidum, B. breve, B. longum and Lactobacillus acidophilus respectively. The inhibitory effect on conjugated diene formation, fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
(18 reference statements)
0
40
0
Order By: Relevance
“…In addition to the modulation of antioxidant enzymes in colonic mucosa cells, antioxidant and MDA-lowering effects of dietary fiber could be mediated by its prebiotic properties, i.e., promoting the growth of bifidobacteria and lactobacilli [7]. It has been shown that these strains are able to reduce lipid peroxidation by increasing free radical scavenging ability and ferric-chelating capacity [60,61]. These mechanisms might explain our results on MDA-lowering effects of different nuts in FS.…”
Section: Discussionmentioning
confidence: 49%
“…In addition to the modulation of antioxidant enzymes in colonic mucosa cells, antioxidant and MDA-lowering effects of dietary fiber could be mediated by its prebiotic properties, i.e., promoting the growth of bifidobacteria and lactobacilli [7]. It has been shown that these strains are able to reduce lipid peroxidation by increasing free radical scavenging ability and ferric-chelating capacity [60,61]. These mechanisms might explain our results on MDA-lowering effects of different nuts in FS.…”
Section: Discussionmentioning
confidence: 49%
“…Our study provides new information of relevance to ␤-mannan conversion by the human gut microbiota. B. adolescentis can grow, for example, on glucose, mannose, and galactose (53) and both hydrolyzed and unhydrolyzed konjac glucomannan (31,54). Until now, however, the enzymes responsible for mannan saccharification have not been characterized in any detail.…”
Section: Discussionmentioning
confidence: 99%
“…In general, bifidobacteria have the capacity to metabolize various complex carbohydrates (28). At least some of the strains, including Bifidobacterium adolescentis, can grow on glucomannan and glucomannan oligosaccharides (31). However, the putative enzyme(s) responsible for ␤-mannan depolymerization in the human gut is largely unknown, although Bacteroides ovatus produces ␤-mannanase activity when grown on galactomannan (32,33).…”
mentioning
confidence: 99%
“…Connolly et al, (2010) described that populations of different beneficial bacteria such as Bifidobacterium genus, the Lactobacillus-Enterococcus group and the Atopobium group can be significantly increased after konjac glucomannan hydrolysate fermentation. Fermentation of konjac glucomannan and hydrolyzed konjac glucomannan may protect against oxidative stress in the human colon (Wang et al, 2008). Mizutani and Mitsuoka (1982) evaluated the effect of 10% konjac based diet on total fecal microflora count in 30 male C3H/He mice.…”
Section: Prebiotic Effectsmentioning
confidence: 99%